2019
DOI: 10.4103/jfmpc.jfmpc_350_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of medication adherence and its associated factors among patients with noncommunicable disease in rural Puducherry, South India – A facility-based cross-sectional study

Abstract: Background:Trends in morbidity and mortality due to noncommunicable diseases (NCDs) are rising because of poor control status. Medication nonadherence is one of the most common and modifiable causes of inadequate control status.Objectives:To determine the prevalence of drug adherence among patients with NCD in rural Puducherry.Methods:A facility-based cross-sectional study was done among 260 patients with NCD receiving treatment from rural primary health center in Puducherry during February and March 2018. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 8 publications
1
14
1
Order By: Relevance
“…24 In this study, 39% reported poor adherence. The prevalence of poor adherence in the present study was similar to the studies reported from India, 19,25,26 Brazil, 27 Ethiopia, 28 and Tanzania. 29 In contrast to our findings, a study from Kerala, India, reported a much higher prevalence (74%), but the study was reported from a general population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…24 In this study, 39% reported poor adherence. The prevalence of poor adherence in the present study was similar to the studies reported from India, 19,25,26 Brazil, 27 Ethiopia, 28 and Tanzania. 29 In contrast to our findings, a study from Kerala, India, reported a much higher prevalence (74%), but the study was reported from a general population.…”
Section: Discussionsupporting
confidence: 90%
“…11,18 Previous studies have reported medication adherence in primary health care or community settings in India. 13,19 However, evidence from public sector tertiary care hospitals on PWDs medication adherence and its relationship with glycemic control status from the south Indian population are limited. Hence in this study, we aimed to assess the medication adherence and glycemic control status among PWDs seeking care from a public sector tertiary care hospital, Puducherry, south India.…”
Section: Introductionmentioning
confidence: 99%
“…Although 39.4% of the participants were found to be nonadherent to their prescribed medications, more than two-thirds of the participants were found to be nonadherent to a healthy lifestyle and follow-up advice. Nonadherence to medication was found to be slightly less in our study compared to the study done in rural Karnataka, India (43.5%) by Kumar et al 5 A previous study in Puducherry, India by Yuvaraj et al 18 elicited increasing age and female gender to be significantly associated with poor medication adherence among patients with NCDs. Our study also found a similar association not only with regard to medication nonadherence but also with nonadherence to a healthy lifestyle and follow-up advice.…”
Section: Discussioncontrasting
confidence: 67%
“…2 Drug noncompliance is a major issue in the management of patients with noncommunicable diseases. 3 Compliance with therapy is a primary determinant of treatment success. Noncompliance is a serious problem that not only affects the patient but also the health-care system.…”
Section: Introductionmentioning
confidence: 99%